Health Benefits of Pumpkin Seed and Nutrition Profile of 35 Pumpkin Accessions - Geoffrey M. Meru; Yuqing Fu; Dayana Leyva; Paul Sarnoski; Yavuz Yagiz (EDIS)
This article aims to summise production and nutrition aspects of pumpkin seed. Specifically, it focuses on health benefits of the seeds, production practices and provides data on the oil, protein and fatty acid composition of 35 pumpkin accessions.